ANALISIS YURIDIS TERHADAP MEKANISME PEMBAYARAN INTERNASIONAL DALAM TRANSAKSI GLOBAL - Tanjung Pamungkas (PT. Saha Kreasi Indonesia, 2026)
The development of globalization has driven an increase in increasingly complex international trade transactions, necessitating an effective, secure, and legally certain international payment mechanism. This research aims to analyze the regulation of international payment mechanisms from the perspective of international law, examine their application in global transaction practices, and identify the role of international law in providing legal protection and dispute resolution for the parties involved. The research method used is normative legal research with a statutory approach and a conceptual approach. The sources of legal materials consist of primary, secondary, and tertiary legal materials collected thru library research and analyzed qualitatively. The research results show that international payment mechanisms are regulated thru various legal instruments, both hard law and soft law, such as rules formulated by the International Chamber of Commerce and international conventions like the United Nations Convention on Contracts for the International Sale of Goods. The application of payment mechanisms such as Letters of Credit, telegraphic transfers, and documentary collections in global transaction practices demonstrates variations tailored to the needs and risk levels of the parties involved. International law plays a crucial role in creating certainty and legal protection thru general principles, regulation of rights and obligations, and the provision of dispute resolution mechanisms, including international arbitration supported by the Convention on the Recognition and Enforcement of Foreign Arbitral Awards. Nevertheless, there are still various obstacles such as differences in legal systems between countries and the development of digital payment technology that have not yet been fully accommodated within the existing legal framework.